Combined influence of polymorphic variants of PPAR-2 (rs1801282) and ACE (rs4646994) genes on the onset of non-alcoholic fatty liver disease in patients with essential arterial hypertension and obesity - Yu. M. Yarynych; L. P. Sydorchuk (Kazimierz Wielki University, 2018)
Objective: to study a combined influence of polymorphic variants of PPAR-g2 (rs1801282) and ACE (rs4646994) genes on the onset of non-alcoholic fatty liver disease (NAFLD) in patients with essential arterial hypertension (EAH) and obesity. Materials and methods: The study involved 96 patients with NAFLD, stage II EAH of the 1-2 degrees, with high and very high risk with associated AO including males - 41.67% (40), women - 58.33% (56), the average age was 53.70 ± 5.34 years. The function of the liver was studied by the activity of organ-specific enzymes. The polymorphism of PPAR-g2 (Pro12Ala) and ACE (I / D) genes was studied  by the PCR method. The control group consisted of 50 virtually healthy individuals. Results. A third of patients with NAFLD (31.25%) are carriers of an unfavorable combination of homozygous deletion of the ACE gene (rs4646994) and the ProPro genotype of the PPAR-g2 gene (rs1801282) (DD / Pro12), and one in five (22.92%) is a carrier of a heterozygote combination for two genes (ID / ProAla variant), which is by 2.6 and 2.9 times more frequent than in the control group (p = 0.01 and p = 0.025, respectively). The controls are dominated by individuals with a combination of the ID-polymorphic variant of the ACE gene and the ProPro genotype of the PPAR-γ2 gene by 1.84 times: 44.0% versus 23.96% (c2=6,19, р=0,013). The risk of NAFLD in the surveyed population of the inhabitants of Northern Bukovyna increases with a combination of the Ala allele of the PPAR-g2 gene and the ID-genotype of the gene ACE (ID / ProAla, ID / 12Ala variants) by 2.3 times (OR = 3.17, 95% CI OR = 1.13-8.88, p = 0.023), due to NASH - by 4.4 times (OR = 7.0, 95% CI OR = 1.81-27.07, p = 0.006). While the dominant effect of the homozygous deletion of the ACE gene, without the significant effect of the Pro12-genotype of the PPAR-γ2 gene, on the owners of the DD / Pro12 variant, increases the risk of NAFLD by 2.6 times (OR = 3.33, 95% CI OR = 1.28 -8.68, p = 0.01), due to NALS - by 2.7 times (OR = 3.53, 95% CI OR = 1.33-9.34, p = 0.008), respectively. Instead, the combination of the I-allele of the ACE gene and the Pro-allele of the PPAR-γ2 gene is protective with the lowest chance of NAFLD (OR = 0.40, 95% CI OR = 0.19-0.83, p = 0.013) and its subtypes, especially steatohepatitis (OR = 0.08, 95% CI OR = 0.01-0.69, p = 0.006) than liver steatosis (OR = 0.48, 95% CI OR = 0.23-1, 01, p = 0,051). Conclusions: Having the DD genotype of the ACE gene in combination with the Pro12 genotype of the PPAR-γ2 gene increases the risk of NAFLD by 2.6 times (due to non-alcoholic liver steatosis). The combination of the I-allele of the ACE gene and the Pro-allele of the PPAR-γ2 gene is protective with the lowest chance of NAFLD in the population (especially of non-alcoholic steatohepatitis).